2007
DOI: 10.1182/blood-2007-02-073536
|View full text |Cite
|
Sign up to set email alerts
|

Neurologic complications associated with intrathecal liposomal cytarabine given prophylactically in combination with high-dose methotrexate and cytarabine to patients with acute lymphocytic leukemia

Abstract: Neurologic complications associated with intrathecal liposomal cytarabine given prophylactically in combination with high-dose methotrexate and cytarabine to patients with acute lymphocytic leukemiaElias Jabbour and colleagues reported on the novel use of intralumbar liposomal extended-release ara-C (DepoCyt; SkyePharma, San Diego, CA) administered in lieu of standard central nervous system (CNS) prophylaxis for adult patients with acute lymphocytic leukemia (ALL). 1 Concerningly, 5 of the 31 patients receivin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
12
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(13 citation statements)
references
References 3 publications
0
12
1
Order By: Relevance
“…Tolerability was good, and mild headache was the only adverse effect, similar to other case reports (Miller et al, 1997;Knop et al, 2005). It is interesting that there were no neurological side effects in the three patients who received concurrent high-dose systemic chemotherapy, contrary to other authors' findings (Chamberlain & Glantz, 2007;Jabbour et al, 2007;McClune et al, 2007). In summary, these are the first results on the effectiveness of the sustained-release formulation of liposomal cytarabine for CNS involvement in B-CLL and RS.…”
contrasting
confidence: 54%
See 2 more Smart Citations
“…Tolerability was good, and mild headache was the only adverse effect, similar to other case reports (Miller et al, 1997;Knop et al, 2005). It is interesting that there were no neurological side effects in the three patients who received concurrent high-dose systemic chemotherapy, contrary to other authors' findings (Chamberlain & Glantz, 2007;Jabbour et al, 2007;McClune et al, 2007). In summary, these are the first results on the effectiveness of the sustained-release formulation of liposomal cytarabine for CNS involvement in B-CLL and RS.…”
contrasting
confidence: 54%
“…Although several studies have demonstrated the efficacy of the IT formulation of liposomal cytarabine in the treatment of neoplastic meningitis in acute leukaemia and lymphoma (Glantz et al, 1999;Sancho et al, 2007;Garcia-Marco et al, 2009), no reports on its effectiveness for leptomeningeal involvement in B-CLL or RS have been published. To the best of our knowledge, of all reported cases of CLL with CNS involvement, only one patient received treatment with IT depot liposomal cytarabine.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Admittedly, it is diffi cult to distinguish symptoms by infi ltration of CNS from side effects observed after administration of any substance available for intrathecal use alone or in combination with systemic chemotherapy (Weiss et al 1974;Resar et al 1991;Schiller et al 1992;Benesch and Urban 2008). Nevertheless, these observations have led to a discussion among clinicians about the safety of DepoCyte ® (Chamberlain and Glantz 2007;Pui 2007). …”
Section: Treatment Results With Liposomal Encapsulated Cytarabinementioning
confidence: 99%
“…Methotrexate is known as a strong classic anticancer agent and used as monotherapy or in combination with other anticancer drugs in multidrug chemotherapy regimens (3). It has a wide range of activities in cytostatic activities, especially when high doses are associated with the release of folinic acid (4)(5)(6). Serum concentrations of methotrexate quickly drop when it is directly injected into the bloodstream (7).…”
Section: Introductionmentioning
confidence: 99%